Garland of divine flowers selected devotional lyrics of Saint Jnanesvara - Jnanesvara 1290.; Bobade, P. V. (Delhi Motilal Banarsidass, 1987)
Prose translations of selected abhacngas, a genre of Marathi poetical composition.
Includes index.
Poems.
Keywords: Jnanesvara -- fl. 1290 -- Translations into English